KISAH DALAM ALQURAN SEBAGAI MATERI DAKWAH - Siti Musyahidah (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2014)
One component of Islamic da’wah is the content that is essential for the effective implementation of da’wah. Without content, it is impossibe for da’wah to be carried out effectively, and the goal will not be achieved. God gives a reference for the Muslim preacher to make the Qur'an as a source of da’wah materials, since in the Qur'an there are a variety of science, stories (qasas) of the prophets and their people, ashab al-kahf, and so forth. All of this can be used as da’wah materials. Moreover, the Qur'an compiled the stories in certain categories, so it is so easily to take advantage, advice and values from it that can shape the quality of faith and piety.